Comparative Study of the Biphasic Behavior of Cyanex301 and Its Two Analogs by Molecular Dynamics Simulations. Issue 4 (16th February 2020) - Wang, Qin; Xia, Miaoren; Liu, Ziyi; Song, Yu‐Fei; Chai, Zhifang; Wang, Dongqi
Abstract: Cyanex301 is considered as an important extractant in liquid–liquid extraction, while its dynamics in condensed phase remains unclear. By means of molecular dynamics simulations, the biphasic behavior of Cyanex301 in water–toluene binary solvents is addressed and compared to that of its two analogs, Cyanex272 and Cyanex302. The simulations shows that deprotonated ligands retard the de‐mixing of the binary solvents compared to their neutral counterparts, but display higher surface activity, and assemble in a more orderly manner at the interface. Increasing their concentrations results in the formation of microtubule‐like structures to maximize their contact with aqueous phase, which is not observed for their native states. The presence of counterion Na + "salts out" ligands and enhances their distribution at the interface. This work complements experimental studies of the ligands with details of their conformations and distributions at the molecular level, and is expected to contribute to the extensive development of their applications in hydrometallurgy. Abstract : The biphasic behavior of Cyanex301 is addressed by molecular dynamics simulations. It displays higher surface activity in its deprotonated state than in its native state, and can form micelle‐like aggregates at high concentration to maximize its contact with aqueous phase. The presence of Na + "salts out" Cyanex301 and enhances its distribution at the interface. Cyanex272 and Cyanex302 are also studied for comparison.